ANALYSIS OF LOCAL CULINARY CONSUMPTION ON THE ATTRACTIVENESS OF CULINARY TOURISM IN THE SURYA KENCANA AREA OF BOGOR - Gabriella Aimee Kristyadi; Dewanta Facrureza (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Currently, local culinary in Indonesia is popular and a highlight for tourists. Local cuisine is no less interesting than other culinary that looks more interesting. Each region has its own distinctive culinary. Local cuisine does not only serve food or drinks, but local cuisine offers many uniqueness and various culinary flavors. One of the things that provide the most memorable experience for tourists is when tourists come and taste the typical culinary of tourist areas, either eating on the spot or to take home as souvenirs. This research method uses a descriptive qualitative approach. Data collection is taken by conducting interviews, observations and documentation. The purpose of the study was to determine the relationship between local culinary consumption and the attractiveness of culinary tourism in the Surya Kencana Area of Bogor. Local culinary consumption in this study includes five dimensions, namely the influence of food ingredients, the influence of cooking techniques, distinctive tastes, food traditions and rituals and cultural heritage. The subjects of this study are tourists who are interested in coming or have visited the Surya Kencana Bogor Area. Based on the results of interviews, the interviewees showed that the data collected proved that the typical culinary of Bogor City in the Surya Kencana Area of Bogor is a culinary tourism center that attracts tourists to visit.